Malecón turístico de Girardot. Recuperación de la ronda del Río Magdalena. - Salas Henao, Rubén Camilo (Universidad Antonio Nariño, 2021)
The following work of degree, consists of the description, analysis and approach of an urban proposal, in order to give solution or answer to the main environmental, social and urban problems that are presented specifically on the banks of the Magdalena river, in the commune 3 of the city of Girardot - Cundinamarca. From an analysis of the invasion of the Magdalena river bank and the effects that this phenomenon causes in the environmental, social and urban areas. This project arises from the need to intervene in a sector that has undergone different changes over time, and that due to its strategic location is an important sector for the development of the city of Girardot and nearby municipalities.